El gasto del sector educación y los logros educativos del departamento Loreto, periodo 2014-2018 - Burga Flores, Sadith Janeth (2021)
The development of the Education sector is essential for the population of a country or region to achieve better living standards. The objective of this thesis was to determine the relationship between the expenditure of the Education sector and the educational achievements of the department of Loreto, in the period 2014 - 2018. With this purpose, the present investigation of Quantitative type, Correlational level and of Non-Experimental design. The research concludes that there is no relationship between spending in the Education sector and educational attainment, since the statistical test of the relationship between spending and level of education achieved by the population aged 15 years or more, has a Correlation Coefficient of r = -0.071605206 and a Determination Coefficient of R2 = 0.005127305; the relationship between spending and the average years of study achieved shows a Correlation Coefficient of r = 0.2496649861 and a Determination Coefficient of R2 = 0.062325053; and the relationship of spending with the illiteracy rate results in a Correlation Coefficient of r = 0.319937033 and a Determination Coefficient of R2 = 0.422296739. Likewise, the majority of the population aged 15 years or over has reached a “Secondary” level of education (46.08%). The average number of years of study achieved by Loreto's population aged 15 and over is 9 years, below the national average of 10.2 years. Illiteracy rate is 6.68%, while at the national level it is 5.94%.